Analysis of Power Generation Potential of Kaidu River Cascade Hydropower Stations Based on Simulation-Optimization Dispatching Framework - CHEN Hongbo; BAI Tao; HUA Xin; LIU Rui; KANG Yu (Renmin Zhujiang)
The annual trading declaration of the electricity market for Kaidu River Cascade Hydropower Station depends on an accurate assessment of their power generation capacity. In order to fully tap the power generation dispatching potential of the hydropower station, rationally declare the annual power generation plan, and guarantee the economic benefits of the hydropower station, it is imperative to carry out research on the power generation dispatching potential of Kaidu River Cascade Hydropower Station. This study focused on Kaidu River Cascade Hydropower Station, aiming to minimize water shortage rates and maximize power generation. A multi-objective optimization dispatching model was created, and it was solved by using an improved NSGA-II algorithm. The model results were compared with simulated dispatching to tap the power generation of optimization dispatching. The results show that: ① Compared with simulation dispatching, optimization dispatching improves output reliability and increases power generation. Under simulation dispatching, the annual average power generation of Kaidu River Cascade Hydropower Station is 1.678 billion kW·h. Optimization dispatching obtains an additional 133 million kW·h (8% increase) in the annual average power generation; ② in different typical years, optimization dispatching has different effects on power generation dispatching potential exploitation of Kaidu River Cascade Hydropower Station, especially in extreme dry years, where the increase is 1.95 times that of normal years and 6.68 times that of extreme wet years. These results provide a decision-making basis for annual trading plan declarations of cascade hydropower stations and ensure the economic benefits of cascade hydropower stations.